Indonesia’s Incentive Policies on Electric Vehicles: The Questionable Effort from the Government - Yuniza, Mailinda Eka; Pratama, I Wayan Bhayu Eka; Ramadhaniati, Rahmah Candrika (International Journal of Energy Economics and Policy, 2021)
This study seeks to solve the problems in the development of electric vehicles in Indonesia and focuses on incentive policies with related theories compared with other countries. As an effort to realize an environmentally friendly industry, electric vehicles have become a global trend for states to develop, including in Indonesia. Electric vehicles as new discourse in Indonesia needs great support from the Government. In 2022, Indonesia itself targets the first production of domestic electric cars. In 2025, electric cars in Indonesia are targeted to reach 20% of the market. In this case, the Indonesian Government has sought to provide incentives for accelerating the development of electric vehicles through President Regulation Number 55 of 2019 regarding the Acceleration of the Battery Electric Vehicle Program for Road Transportation. However, this policy has not yet become a trigger mechanism for the public to switch to electric vehicles. The determinant factor for this adversity would be; there is a lack of incentives offered by the Government that can be obtained by the consumers. The author finds that the incentive policy provided through Government Regulation is still questionable because it has not been able to trigger the public to switch to electric vehicles. Keywords: Energy; Electric Vehicle; Incentives; Transportation; Indonesia. JEL Classifications: K4, R5 DOI: https://doi.org/10.32479/ijeep.11453